Evolving Halal Certification Regulations and Indonesia'S Competitive Position in the Global Halal Market: Challenges and Opportunities for Market Access - Tanty Yuanita; Roma Nova Cahjati Poetry (Greenation Research & Yayasan Global Resarch National, 2025)
Halal certification plays a crucial role in enhancing economic competitiveness forcountries with substantial Muslim populations, and Indonesia is making significant efforts tostrengthen its standing in the rapidly expanding global halal market. This study exploresrecent policy reforms within Indonesia's halal certification framework and examines theirimplications for the country's competitiveness and access to international markets. Through aqualitative analysis of regulatory updates, government policy initiatives, and industry data, the research assesses changes in certification procedures, implementation strategies, andsectoral developments influencing market access. The findings highlight that recentgovernment policy reforms have markedly streamlined certification processes, expandedopportunities for Micro, Small, and Medium Enterprises (MSMEs), and reduced barriersthrough initiatives like the SEHATI program, which provides free certification for select non- critical product categories. These efforts have improved operational efficiency, encouragedbroader MSME participation, and facilitated Indonesia's growth into halal sectors beyondfood, including pharmaceuticals and cosmetics. Evidence of export growth and an enhancedinternational presence further reflect these positive developments in market access. Nonetheless, challenges remain in fully aligning Indonesia's certification system withinternational halal standards, managing certification costs, and boosting competitiveness inemerging halal industries. Continued refinement of regulations, deeper harmonization withglobal standards, and strengthened institutional support for MSMEs are essential forIndonesia to seize new opportunities within the global halal economy and sustain itsleadership role.